Analysis of Arc Re-Ignition in Vacuum Interrupter-Based HVdc Circuit Breakers - Tamer Eliyan; Ali Saeed Almuflih; Z. M. S. Elbarbary; Fady Wadie (IEEE Access)
The protection of HVdc systems has long been challenged by the absence of natural current zero-crossing, typically addressed using L-C branches. However, the phenomenon of multiple arc reignitions in vacuum interrupter (VI) based HVdc circuit breakers (CBs) has been insufficiently investigated in existing literature. This paper addresses this gap by systematically analyzing the arc-reignition phenomenon in VI-HVdc-CBs, focusing on the impact of inductance (L), capacitance (C), and resistance (R) on arc reignitions, arcing time, and transient recovery voltage (TRV). A seven-phase testing methodology is used to explore these parameters. The results show that increasing L reduces arc reignitions but increases arcing time, with 0.5 mH identified as the optimal value for L. In contrast, increasing C significantly reduces both TRV and arcing time, with $200~μ $ F selected as the optimal capacitance. Resistance (R) had minimal effect on TRV and arcing time once optimal L-C values were set. The paper further extends the investigation by evaluating active L-C branches and multi-injection methods. The results indicate that active L-C branches improve performance, but the multi-injection method outperforms both passive and active designs, achieving the lowest TRV and arcing time. This work provides novel insights into the arc-reignition behavior of VI-HVdc-CBs and offers practical guidelines for optimizing HVdc circuit breaker performance, aiming to minimize arc reignitions, TRV, and arcing time for more reliable HVdc system protection.